Neuroradiology of infectious diseases. Issue 3 (June 2021) - Singh, Sonia Kaur; Hasbun, Rodrigo
Abstract : Purpose of review: Early diagnosis of central nervous system (CNS) infections is crucial given high morbidity and mortality. Neuroimaging in CNS infections is widely used to aid in the diagnosis, treatment and to assess the response to antibiotic and neurosurgical interventions. Recent findings: The Infectious Diseases Society of America (IDSA) guidelines have clear recommendations for obtaining a computerized tomography of the head (CTH) prior to lumbar puncture (LP) in suspected meningitis. In the absence of indications for imaging or in aseptic meningitis, cranial imaging is of low utility. In contrast, cranial imaging is of utmost importance in the setting of encephalitis, bacterial meningitis, ventriculitis, bacterial brain abscess, subdural empyema, epidural abscess, neurobrucellosis, neurocysticercosis, and CNS tuberculosis that can aid clinicians with the differential diagnosis, source of infection (e.g., otitis, sinusitis), assessing complications of meningitis (e.g., hydrocephalus, venous sinus thrombosis, strokes), need for neurosurgical interventions and to monitor for the response of therapy. Novel imaging techniques such as fast imaging employing steady-state acquisition (FIESTA), susceptibility-weighted imaging (SWI), and chemical exchange saturation transfer (CEST) contrast are briefly discussed. Summary: Though the radiological findings in CNS infections are vast, certain patterns along with clinical clues from history and examination often pave the way to early diagnosis. This review reiterates the importance of obtaining cranial imaging when necessary, and the various radiological presentations of commonly encountered CNS infections.